The Soviet polity; government and politics in the U.S.S.R. - Reshetar, John Stephen (New York : Dodd, Mead, 1971)
From the John Holmes Library collection.
All Ages.
Keywords: Soviet Union -- Politics and government -- 1917-; Soviet Union -- Politics and government; Soviet Union -- Politics and government; Russia -- Politics and government -- 1917-.